Numerical model of solid-phase precipitation in a two-temperature fluid-saturated viscous medium - Pak, Vladimir Vasilievich (Computational Continuum Mechanics, 2012)
A numerical model based on the equations of viscous compaction is developed to investigate solid-phase precipitation taking into account heat and mass transfer between solid and liquid phases. The temperatures of the matrix and fluid differ. The numerical solution is obtained by the finite element method combined with the projection gradient method. Modeling of solid-phase precipitation in the ascending fluid flow reveals that this process plays a significant role in transferring the heat transported by the fluid to the matrix. Geophysical applications of the results obtained confirm their validity in the production of temperature anomalies in the Earth interior.